The assignment of the right to participate in the heritage - Lohmann, Guillermo (2014)
Article 1209 of the Peruvian Civil Code regulates the situation in which the sole heiror any of them decides to transfer all or partof its estate to a third party, including rights and obligations. This is commonly known asan assignment of inheritance.In this article, the author presents a complete analysis on how the assignment of inheritance operates in certain situations, emphasizing in issues related to the liability of the assignee against creditors and the role of the transferor, as well as the necessary formalities for the transference.